Evaluasi Model Kirkpatrick Pada UMKM SIBA Rosella Dalam Meningkatkan Kesejahteraan Keluarga di Tanjung Enim - Lia Oktaviana; Yanti Karmila Nengsih (Jurnal Multidisiplin Dehasen (MUDE), 2023)
The aims of this study is to provide an overview of the evaluation results of the UMKM (MSME) SIBA Rosella program in an effort to improve family welfare in Tanjung Enim. The type of the research is descriptive qualitative that using the Kirkpatrick model evaluation method with 4 levels of evaluation, namely reaction evaluation, learning evaluation, behavior evaluation, and outcome evaluation. The data in this study were obtained through interviews, observation and documentation. There were six research subjects consisting of the chairperson, treasurer, and members of the UMKM. The results of the program evaluation on the reaction evaluation show that; there is a member's reaction to the existing infrastructure and facilities that are adequate, there is a member's reaction to the income or income earned is still lacking and there is a member's reaction to the existing teachers, media and learning strategies that have supported the program. The learning evaluation shows an increase in knowledge, skills and also a change in attitude that occurs in members before and after participating in the program. Behavioral evaluation shows that; there are a change in behavior that causes obstacles, a change in the behavior of mistakes that results in a reprimand, a change in the behavior of active members in teamwork and an increase in performance and understanding of members. Evaluation of the results shows that the number of products sold has not shown sufficient results so that it has an impact on members' income which is still lacking, income is not suitable and economic conditions do not show changes in meeting the economic needs of members, and family needs problems cannot be resolved by members. From the evaluation of the UMKM (MSME) SIBA Rosella program that has been carried out, the results obtained have not been able to support efforts to improve family welfare in Tanjung Enim.